Strength of Silicate-Enamel Coating of Heat Exchanger Pipe - Ibrahimli, E.N. (Herald of Azerbaijan Engineering Academy, 2023)
The examination of the stress state and strength of the silicate-enamel coating of the heat exchanger tube are presented. Formulas are obtained for determining the longitudinal, radial and tangential stresses arising in the sections of the pipe coating. The condition for the strength of the silicate-enamel coating of the pipe under conditions of high temperatures and pressures is presented. The study of the stress state of the silicate-enamel coating of the pipe makes it possible to determine the condition of the strength of the coating of the heat-exchange pipe under the influence of high temperatures and pressures. Analysis of the calculation results shows that the strength of the silicate-enamel coating mainly depends on the geometric dimensions and physical and mechanical characteristics of the heat-exchange tube coating. The obtained calculations make it possible to determine the condition for the destruction of the silicate-enamel coating of the heat exchange tube of the apparatus.